An nc-parac bonding interface damage online detection method based on impedance spectrum

CN122962056APending Publication Date: 2026-10-23HENAN JIAOYUN EXPRESSWAY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611359269.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对上述问题,本发明的目的在于提出一种基于阻抗谱的NC-PARAC粘结界面损伤在线检测方法,解决现有技术中无法对聚合物改性碱激发再生混凝土与既有混凝土粘结界面损伤进行在线、定量、多维度检测的技术问题

Benefits of technology

[0016]本发明的有益效果为:本发明将阻抗谱技术、声发射技术与数字图像相关技术融合应用于NC-PARAC粘结界面损伤检测,实现了从电学响应、能量释放到变形场的多维度同步监测,克服了单一技术信息不完整的缺陷,且通过提取阻抗模值变化率、相位角偏移量及阻抗实部变化量,结合声发射振铃计数与DIC应变场,构建了界面孔隙连通度、微裂纹密度和界面过渡区劣化指数三个综合指标,实现了界面损伤状态的定量表征与五个损伤阶段的在线划分,同时能够识别脆性界面剥离与延性基体断裂两种破坏模式,为水工混凝土结构修复质量的在线评估与服役安全预警提供了技术支撑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962056A_ABST
    Figure CN122962056A_ABST
Patent Text Reader

Abstract

The application discloses an NC-PARAC bonding interface damage online detection method based on impedance spectrum, relates to the technical field of material performance detection, and comprises the following steps: reference impedance spectrum acquisition, load application and multi-source signal synchronous acquisition, impedance spectrum characteristic parameter extraction, multi-source data fusion and damage characterization index construction, damage state online determination and damage mode identification. The application applies impedance spectrum technology, acoustic emission technology and digital image correlation technology to NC-PARAC bonding interface damage detection, realizes multi-dimensional synchronous monitoring from electrical response, energy release to deformation field, and through extraction of impedance modulus change rate, phase angle offset and impedance real part change amount, in combination with acoustic emission ringing count and DIC strain field, three comprehensive indexes of interface pore connectivity, microcrack density and interface transition zone degradation index are constructed, and quantitative characterization of the interface damage state and online division of five damage stages are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material performance testing technology, and in particular to an online detection method for NC-PARAC bond interface damage based on impedance spectroscopy. Background Technology

[0002] Hydraulic concrete structures serve in complex aquatic environments for extended periods, constantly facing multiple challenges including water molecule penetration, inorganic salt ion erosion, and carbonation. This makes them highly susceptible to structural defects such as cracking, erosion, deterioration, and breakage. Freeze-thaw cycles can cause concrete surface spalling and strength reduction; the abrasion and scouring of high-speed, sand-laden water flows can lead to cement paste spalling and aggregate exposure; and cracks caused by alternating wet and dry conditions and stress concentration can further weaken the concrete's load-bearing capacity, seriously threatening the structural safety and long-term service life of engineering projects. Therefore, repairing and reinforcing existing structures with defects is of paramount engineering significance for extending the service life of hydraulic concrete structures.

[0003] Ordinary silicate cement concrete is the most widely used traditional repair material, but its production process results in high carbon emissions, which are particularly pronounced in hydraulic engineering projects due to the massive volume of concrete. Alkali-activated materials, using industrial solid waste such as fly ash and slag powder as precursors, reduce carbon emissions by 60%–80% compared to traditional cement and possess excellent resistance to sulfate attack and freeze-thaw cycles. Crushing waste concrete to prepare recycled aggregate to replace natural aggregate and applying it to alkali-activated recycled concrete can realize the resource utilization of construction solid waste. However, recycled aggregate has high porosity and water absorption, and a weak double-interface transition zone forms between the old mortar layer attached to its surface and the new paste. This leads to a significant deterioration in the interfacial bond performance between alkali-activated recycled concrete and existing concrete (NC), making it difficult to meet the interfacial bond strength requirements for hydraulic structure repair.

[0004] To address the aforementioned issues, existing technologies attempt to modify alkali-activated recycled concrete using polymers. Epoxy resin, due to its good compatibility with inorganic cementitious materials, can fill interfacial pores, refine pore structures, and form organic-inorganic composite networks, and is widely used in the modification research of alkali-activated materials. However, there is currently a lack of effective means for online detection of damage at the bond interface between polymer-modified alkali-activated recycled concrete and existing concrete (NC-PARAC). In existing technologies, impedance spectroscopy can characterize changes in the material's microstructure, acoustic emission can monitor crack initiation and propagation, and digital image correlation (DEM) can obtain the full-field strain distribution, but a single technology cannot comprehensively reflect the damage evolution process at the bond interface. Impedance spectroscopy is sensitive to changes in interfacial pore structure but struggles to locate cracks; acoustic emission can capture crack dynamics but cannot obtain strain field distribution; and DEM can obtain full-field deformation but cannot reflect changes in the deep electrical properties of the interface. Therefore, this invention proposes an online detection method for NC-PARAC bond interface damage based on impedance spectroscopy to solve the problems existing in the prior art. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to propose an online detection method for NC-PARAC bond interface damage based on impedance spectroscopy, thereby solving the technical problem that existing technologies cannot perform online, quantitative, and multi-dimensional detection of bond interface damage between polymer-modified alkali-activated recycled concrete and existing concrete.

[0006] To achieve the objectives of this invention, the invention is implemented through the following technical solution: an online detection method for NC-PARAC bonding interface damage based on impedance spectroscopy, comprising the following steps: S1, Reference Impedance Spectrum Acquisition An AC excitation signal within a preset frequency range is applied to the bonding interface region of the NC-PARAC bonded specimen, and the initial impedance spectrum of the bonding interface region in a non-destructive state is collected. The initial impedance spectrum includes the initial impedance magnitude and the initial phase angle. Before loading the NC-PARAC bonded specimen, an AC signal with a certain frequency range (e.g., 10Hz to 100kHz) is applied to the bonding interface, and the impedance modulus (unit: Ω) and phase angle (unit: °) under the non-destructive state are measured as the baseline for subsequent damage comparison. S2. Load application and synchronous acquisition of multi-source signals A monotonically increasing load was applied to the NC-PARAC bonded specimens, and the following data acquisition operations were performed simultaneously during the loading process: Acoustic emission signals released by NC-PARAC bonded specimens during deformation and failure were collected; Acquire digital image sequences of the surface of NC-PARAC bonded specimens; Real-time impedance spectra of the bonding interface region are continuously acquired at preset time intervals, and the real-time impedance spectra include real-time impedance magnitude and real-time phase angle. By applying a continuously increasing load (such as a displacement rate of 0.2 mm / min) to the NC-PARAC bonded specimen, three types of data were simultaneously collected using an acoustic emission sensor (threshold 45 dB), an industrial camera, and an impedance analyzer to ensure time axis alignment. S3. Extraction of impedance spectrum characteristic parameters The real-time impedance spectrum is compared with the initial impedance spectrum, and the impedance spectrum characteristic parameters are extracted based on the comparison calculation results. The impedance spectrum characteristic parameters include the impedance magnitude change rate, phase angle offset, and the change of the real part of the impedance at the characteristic frequency point. By comparing the real-time impedance spectrum with the initial reference spectrum, the rate of change of impedance modulus (e.g., Δ|Z| / |Z0|), phase angle offset (Δθ), and the change of the real part of impedance at a specific frequency point (e.g., 100Hz or 1kHz) are calculated to reflect the evolution of interface porosity and cracks. S4. Multi-source data fusion and construction of damage characterization indicators Event alignment processing and data correlation analysis are performed on the collected acoustic emission signals, digital image sequences, and extracted impedance spectrum feature parameters to construct a comprehensive damage characterization index, which includes interface pore connectivity, microcrack density, and interface transition zone degradation index. By performing event alignment and correlation analysis on acoustic emission signals (ring count, cumulative ring count), image strain field (maximum principal strain), and impedance characteristics, three comprehensive indicators were obtained: interface porosity connectivity, microcrack density, and interface transition zone degradation index. S5. Online Damage Status Assessment The constructed comprehensive damage characterization index is compared with the preset damage threshold library to determine the current damage state of the bonding interface region of the NC-PARAC bonded specimen. The current damage state includes the elastic deformation stage, microcrack initiation stage, crack stable propagation stage, crack unstable penetration stage, and complete failure stage. By comparing the above comprehensive indicators with a pre-established damage threshold library, it can be determined which stage the interface is in: elastic deformation, microcrack initiation, stable propagation, unstable penetration, or complete failure. S6, Destruction Mode Recognition Based on the changing trends of comprehensive damage characterization indicators, the failure modes of the NC-PARAC bonding interface are identified, including brittle interface peeling failure and ductile matrix fracture failure. Based on the changing trend of the comprehensive indicators (whether it is abrupt or gradual), the failure mode is identified as "brittle interface peeling failure" or "ductile matrix fracture failure".

[0007] A further improvement is made in S3, before extracting the impedance spectrum feature parameters, a data preprocessing operation is performed on the real-time impedance spectrum. The specific steps are as follows: the real-time impedance spectrum is smoothed by a moving average filter with a preset window length, and the interface charge transfer resistance (Rct) and double layer capacitance (Cdl) are extracted by an impedance spectrum fitting method based on an equivalent circuit model (such as an R(CR) or R(Q) model). The equivalent circuit model is composed of solution resistance, interface charge transfer resistance, interface double layer capacitance, and constant phase angle elements connected in series or in parallel.

[0008] A further improvement is made in S4, where the interface pore connectivity is calculated as follows: based on the rate of change of impedance modulus and the phase angle offset in the impedance spectrum characteristic parameters, combined with a preset pore structure-impedance response mapping model, the electrical response is converted into the degree of connectivity between pores (dimensionless value, range 0 to 1), thus obtaining the interface pore connectivity. The pore structure-impedance response mapping model is established based on the Maxwell-Garnett effective medium theory or the Bruggeman effective medium theory.

[0009] A further improvement is made in S4, where the microcrack density is calculated as follows: the acoustic emission signal is processed by parameter extraction to obtain the ring count, cumulative ring count, energy count, and amplitude distribution; digital image correlation calculation is performed on the digital image sequence to obtain the maximum principal strain distribution across the entire field from the DIC calculation; spatiotemporal correlation analysis is performed on the ring count, cumulative ring count, energy count, amplitude distribution, and maximum principal strain distribution across the entire field to count the number of microcracks per unit area (unit: cracks / mm²), thus obtaining the microcrack density.

[0010] Further improvements are made in the following steps for performing digital image correlation calculations on digital image sequences: a speckle field (such as paint or film) with random grayscale distribution is set on the surface of the NC-PARAC bonded specimen. Using the reference image before loading as a benchmark, a zero-mean normalized cross-correlation algorithm (subset size 29×29 pixels, step size 5 pixels) is used to perform subset matching processing on the deformed image after loading to obtain the displacement field of the whole field. The displacement field is then spatially differentiated to obtain the strain field of the whole field. The maximum principal strain distribution is extracted from the strain field of the whole field.

[0011] A further improvement is made in S4, where the interface transition zone degradation index is calculated as follows: based on the change in the real part of the impedance at the characteristic frequency point in the impedance spectrum characteristic parameters, combined with the cumulative ringing count in the acoustic emission signal and the strain localization bandwidth in the digital image sequence, the interface transition zone degradation index (range 0 to 1, the higher the value, the more severe the degradation) is calculated by weighted fusion (the weights are determined by principal component analysis or entropy weight method, such as 0.4, 0.3, 0.3). The weight coefficients of each index in the weighted fusion calculation are determined based on principal component analysis or entropy weight method.

[0012] A further improvement is made in S5, where the preset damage threshold library is established as follows: Destructive tests are conducted on NC-PARAC bonded specimens with different recycled aggregate replacement rates (0%, 50%, 100%) and epoxy resin content (0%, 6%, 8%) in different groups. During the destructive tests, impedance spectra, acoustic emission signals, and digital image sequences are collected simultaneously. The collected data are correlated with the observed microstructure of the SEM / MIP interface after damage. Threshold ranges for impedance spectrum characteristic parameters, acoustic emission signal characteristic parameters, and digital image related characteristic parameters (e.g., impedance modulus change rate <5% indicates the elastic stage, 5%–20% indicates microcrack initiation, etc.) are established for each damage stage, thus forming the preset damage threshold library.

[0013] A further improvement is made in S6, where the specific criteria for identifying the brittle interface peeling failure mode are as follows: The rate of change of impedance modulus in the impedance spectrum characteristic parameters exceeds a first preset rate of change threshold in a first preset time period before the load reaches its peak value, and the phase angle offset exceeds a first preset offset threshold in a second preset time period. Furthermore, the growth rate of the cumulative ring count in the acoustic emission signal exceeds the first preset growth rate threshold during the third preset time period, while the growth rate before the third preset time period is lower than the second preset growth rate threshold. Furthermore, in the maximum principal strain cloud map obtained after digital image correlation calculation of the digital image sequence, there is a continuous high strain band in the bonding interface region. The width of the continuous high strain band is less than a first preset width threshold, and the coverage of the continuous high strain band in the entire length direction of the bonding interface exceeds a first preset coverage threshold.

[0014] A further improvement is made in S6, where the specific criteria for identifying the fracture failure mode of the ductile matrix are as follows: The rate of change of impedance modulus in the impedance spectrum characteristic parameters is lower than the second preset rate of change threshold throughout the entire process of load application, and the rate of change of phase angle offset is lower than the second preset offset threshold throughout the entire process of load application. Furthermore, the second derivative of the cumulative ringing count curve in the acoustic emission signal is positive, and the rate of change of its first derivative continuously decreases throughout the entire process of load application. Furthermore, in the maximum principal strain cloud map obtained after the digital image sequence is obtained by digital image correlation calculation, there are at least two high strain concentration areas that are separated from each other. The area of ​​each high strain concentration area is less than the second preset area threshold, and the minimum distance between any two high strain concentration areas is greater than the preset distance threshold. In addition, there is no continuous high strain band that covers the entire length of the bonding interface and exceeds the second preset coverage threshold.

[0015] A further improvement is that the NC-PARAC bonded specimen is formed by bonding the matrix concrete and the polymer-modified alkali-activated recycled concrete through a bonding interface. The raw materials of the polymer-modified alkali-activated recycled concrete include fly ash, slag powder, alkali activator, natural fine aggregate, natural coarse aggregate, recycled coarse aggregate, waterborne epoxy resin emulsion, curing agent, and defoamer. The replacement rate of the recycled coarse aggregate is 0% to 100%, and the dosage of the waterborne epoxy resin emulsion is 0% to 8%.

[0016] The beneficial effects of this invention are as follows: This invention integrates impedance spectroscopy, acoustic emission, and digital image correlation techniques for the detection of bond interface damage in NC-PARAC, realizing multi-dimensional synchronous monitoring from electrical response and energy release to deformation field. It overcomes the shortcomings of incomplete information from a single technology. Furthermore, by extracting the rate of change of impedance modulus, phase angle shift, and change of the real part of impedance, and combining acoustic emission ringing count and DIC strain field, three comprehensive indicators are constructed: interface porosity connectivity, microcrack density, and interface transition zone degradation index. This enables quantitative characterization of interface damage state and online division of five damage stages. At the same time, it can identify two failure modes: brittle interface peeling and ductile matrix fracture, providing technical support for online assessment of repair quality and service safety early warning of hydraulic concrete structures. Attached Figure Description

[0017] Figure 1 This is a schematic flowchart of the online detection method for NC-PARAC bond interface damage based on impedance spectroscopy of the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] It should be noted that the technical means not described in detail in the following embodiments are all conventional means in the art, are not the key points of the invention, and will not be elaborated upon.

[0020] Example 1 See Figure 1 This embodiment provides an online detection method for NC-PARAC bond interface damage based on impedance spectroscopy. The materials prepared are as follows: In this embodiment, the NC-PARAC bonded specimen is formed by bonding matrix concrete (NC) and polymer-modified alkali-activated recycled concrete (PARAC) through a bonding interface.

[0021] The raw materials for NC are prepared according to the following ratio: P·I42.5 standard cement 349kg / m³ 3 Natural river sand (fineness modulus 2.6) 626 kg / m³ 3 Natural coarse aggregate (particle size 5mm~20mm) 1164kg / m³ 3 210 kg / m³ of mixing water 3 The compressive strength of the NC cube is 33.21 MPa.

[0022] PARAC raw materials are prepared according to the following ratio: fly ash (Grade I) 300kg / m³ 3 Slag powder (S95 grade) 200kg / m³ 3 Water glass (initial modulus 3.29, adjusted to 1.3) 158.1 kg / m³ 3 Sodium hydroxide (99.6% purity) 25.4 kg / m³ 3 Mixing water 68.2 kg / m 3 Additional water 20.3 kg / m 3 Natural river sand 644.6 kg / m³ 3 Natural coarse aggregate (particle size 5mm~10mm) 483.4kg / m³ 3 Recycled coarse aggregate (particle size 5mm~10mm) 483.4kg / m³ 3 Waterborne epoxy resin emulsion (bisphenol A type, solid content 50%) 60.0 kg / m³ 3 Polyamide curing agent 30.0 kg / m 3 0.6 kg / m³ of silicone defoamer 3 The mass ratio of fly ash to slag powder is 3:2, the mass ratio of water to precursor is 0.45, the sand ratio is 40%, the recycled coarse aggregate replacement rate is 50%, and the epoxy resin content is 6%.

[0023] The preparation process of NC-PARAC bonded specimens is as follows: First, cast the NC matrix, cure it under standard conditions for 28 days, and then place it in a natural environment for 3 months; perform groove treatment on the NC bonding interface (groove depth 8mm, spacing 30mm); place the NC specimen into the mold, and apply epoxy resin interface agent to its surface (coating thickness ≤2mm); then cast PARAC, vibrate to form, and cure it under standard conditions for 28 days.

[0024] The specific steps are as follows: S1, Reference Impedance Spectrum Acquisition Before loading the NC-PARAC bonded specimen, four copper electrodes (50 mm apart) were symmetrically arranged on both sides of the bonding interface area. An impedance analyzer (frequency range 10 Hz to 100 kHz, AC voltage amplitude 100 mV) was used to apply an AC excitation signal to the electrodes, and the initial impedance spectrum under non-destructive conditions was collected. The initial impedance modulus |Z0|(f) and the initial phase angle θ0(f) were recorded, where f is the frequency point, and a total of 100 logarithmically uniformly distributed frequency points were collected.

[0025] S2. Load application and synchronous acquisition of multi-source signals The NC-PARAC bonded specimens were placed on a universal testing machine, and a three-point bending loading method (support span 300 mm) was applied using displacement control mode with a monotonically increasing load at a loading rate of 0.1 mm / min. The following data acquisition operations were performed simultaneously during the loading process: (1) Acoustic emission signal acquisition: Two acoustic emission sensors (resonant frequency 150kHz) were attached to the surface of the specimen 20mm from the bonding interface on both sides. High vacuum grease was filled between the sensors and the specimen as a coupling agent. A Micro-II type acoustic emission acquisition system was used, with a preamplifier gain of 40dB, a threshold set to 45dB, and a sampling frequency of 1MHz. Parameters such as ring count, cumulative ring count, energy count, and amplitude were acquired in real time.

[0026] (2) Digital image sequence acquisition: Random black and white speckles were sprayed on the bonding interface area (100mm×100mm) on the front side of the specimen. A digital image sequence of the specimen surface during loading was continuously captured using an industrial camera (resolution 2048×2048 pixels, sampling frequency 10 frames / second).

[0027] (3) Real-time impedance spectrum acquisition: Repeat the impedance spectrum acquisition operation in step two at 30-second intervals to obtain the real-time impedance spectrum at each time point, including the real-time impedance magnitude |Zt|(f) and the real-time phase angle θt(f).

[0028] S3. Extraction of impedance spectrum characteristic parameters Data preprocessing was performed on the acquired real-time impedance spectrum: a moving average filter with a window length of 5 was used to smooth the real-time impedance magnitude and real-time phase angle; an equivalent circuit model Rs(Cdl(RctQ)) was used to fit the impedance spectrum (where Rs represents the solution resistance, Cdl represents the interface double layer capacitance, Rct represents the interface charge transfer resistance, and Q represents the constant phase angle element), and the interface charge transfer resistance Rct and the interface double layer capacitance Cdl were extracted.

[0029] Then, the following impedance spectrum characteristic parameters are calculated: (1) The rate of change of impedance modulus Δ|Z|(f) is calculated using the following formula: Δ|Z|(f)=[|Zt|(f)-|Z0|(f)] / |Z0|(f)×100% Where f represents the frequency point, |Zt|(f) represents the real-time impedance magnitude at frequency f, |Z0|(f) represents the initial impedance magnitude at frequency f, and Δ|Z|(f) represents the rate of change of the impedance magnitude at frequency f. In this embodiment, the value at the characteristic frequency point f=1kHz is taken as representative.

[0030] (2) The phase angle offset Δθ(f) is calculated using the following formula: Δθ(f) = θt(f) - θ0(f) Where θt(f) represents the real-time phase angle at frequency f, θ0(f) represents the initial phase angle at frequency f, and Δθ(f) represents the phase angle offset at frequency f. In this embodiment, the value is taken at the characteristic frequency point f=1kHz.

[0031] (3) The change in the real part of the impedance at the characteristic frequency point, ΔZreal, is calculated using the following formula: ΔZreal=Zreal t (1kHz)-Zreal0(1kHz) Among them, Zreal t (1kHz) represents the real part of the impedance at a frequency of 1kHz, Zreal0(1kHz) represents the initial real part of the impedance at a frequency of 1kHz, and ΔZreal represents the change in the real part of the impedance.

[0032] S4. Multi-source data fusion and construction of damage characterization indicators Event alignment processing was performed on the acoustic emission signals, digital image sequences, and impedance spectrum characteristic parameters (using the loading time axis as a reference, unifying the acquisition times of all data to the same time coordinate system). Then, the following three comprehensive damage characterization indices were constructed: (1) Interface pore connectivity Pc: Based on the rate of change of impedance modulus Δ|Z| (1kHz) and phase angle offset Δθ (1kHz), and combined with the pore structure-impedance response mapping model established based on Maxwell-Garnett effective medium theory, the interface pore connectivity Pc is calculated. The calculation formula is: Pc=α·[Δ|Z| / (100+Δ|Z|)]+β·[Δθ / (90+Δθ)] Where Δ|Z| represents the rate of change of impedance magnitude at 1kHz (unit: %), Δθ represents the phase angle offset at 1kHz (unit: °), α represents the weighting coefficient of the impedance magnitude term (0.6 in this embodiment), β represents the weighting coefficient of the phase angle offset term (0.4 in this embodiment), and Pc represents the interface pore connectivity, with a value range of [0,1]. The larger the value, the higher the degree of pore connectivity.

[0033] (2) Microcrack density ρ: Ringing count CR, cumulative ringing count ΣCR, energy count CE, and amplitude distribution are extracted from the acoustic emission signal; the maximum principal strain εmax is obtained by performing digital image correlation calculation from the digital image sequence. The specific steps of digital image correlation calculation are as follows: using the reference image before loading as a benchmark, the zero-mean normalized cross-correlation algorithm (subset size 29×29 pixels, step size 5 pixels) is used to perform subset matching on the deformation image to obtain the displacement field of the whole field; the displacement field is spatially differentiated to obtain the strain field of the whole field; the maximum principal strain εmax is extracted from the strain field of the whole field. Then, the ringing count CR, cumulative ringing count ΣCR, energy count CE, amplitude distribution, and the maximum principal strain εmax of the whole field are subjected to spatiotemporal correlation analysis (a 5mm×5mm window is taken in the bonding interface area, and the number of acoustic emission positioning events and the number of pixels with strain exceeding 0.1% are counted in the window), and the microcrack density ρ (unit: cracks / mm) is calculated. 2 The formula for calculating ρ is: ρ=(N AE +N DIC ) / A Where, N AE N represents the number of acoustic emission localization events within the window (unit: events). DIC The number of pixels (in units) within the window whose maximum principal strain is greater than 0.1% is represented by A, where A represents the window area (25 mm² in this embodiment). 2 ρ represents the microcrack density.

[0034] (3) Interface transition zone degradation index DITZ: Calculated by weighted fusion based on the impedance real part change ΔZreal at the characteristic frequency point (1kHz), the cumulative acoustic emission ringing count ΣCR, and the DIC strain localization bandwidth w. The calculation formula is: DITZ=γ1·(ΔZreal / ΔZmax)+γ2·(ΣCR / ΣCRmax)+γ3·(w / wmax) Wherein, ΔZreal represents the change in the real part of impedance (unit: Ω), and ΔZmax represents the preset maximum reference value for the change in the real part of impedance (in this embodiment, the maximum value among all test samples is taken, unit: Ω); ΣCR represents the cumulative ring count of acoustic emission (unit: rings), and ΣCRmax represents the preset maximum reference value for the cumulative ring count (in this embodiment, the maximum value among all test samples is taken, unit: rings); w represents the DIC strain localization bandwidth (defined as the width of a continuous region where the maximum principal strain is greater than 30% of the peak strain, unit: mm), and wmax represents the preset maximum reference value for the strain localization bandwidth (in this embodiment, the maximum value among all test samples is taken, unit: mm); γ1, γ2, and γ3 represent weighting coefficients, determined based on principal component analysis. In this embodiment, γ1 = 0.35, γ2 = 0.40, and γ3 = 0.25; DITZ represents the interface transition zone degradation index, with a value range of [0,1]. The larger the value, the more severe the degradation of the interface transition zone.

[0035] S5. Online Damage Status Assessment The preset damage threshold library is established as follows: Multiple groups of NC-PARAC bonded specimens with different recycled aggregate replacement rates (0%, 25%, 50%, 75%, 100%) and epoxy resin content (0%, 2%, 4%, 6%, 8%) are subjected to destructive tests. Impedance spectra, acoustic emission signals, and digital image sequences are simultaneously collected. The collected data are then correlated with post-damage interface scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) pore structure observations to establish threshold ranges for impedance spectrum characteristic parameters, acoustic emission signal characteristic parameters, and digital image related characteristic parameters for each damage stage, thus forming the preset damage threshold library. In this embodiment, some key thresholds in the damage threshold library are as follows: The calculated Pc, ρ, and DITZ values ​​from step five are compared with the aforementioned threshold library to determine the current damage state. In this embodiment, when the load reaches 50% of the peak load, Pc = 0.12 and ρ = 0.3 damage points / mm. 2 DITZ=0.08, indicating the elastic deformation stage; when the load reaches 75% of the peak load, Pc=0.28, ρ=1.2 strips / mm 2 DITZ=0.22, indicating the microcrack initiation stage; when the load reaches 90% of the peak load, Pc=0.52, ρ=4.1 cracks / mm. 2The DITZ value is 0.48, indicating a stable crack propagation stage. When the load reaches the peak load, Pc = 0.78 and ρ = 8.3 cracks / mm. 2 The DITZ value is 0.72, indicating that the crack is in an unstable and continuous stage.

[0036] S6, Destruction Mode Recognition Based on the changing trends of comprehensive damage characterization indices, the failure modes of the NC-PARAC bonding interface are identified.

[0037] If the following first set of conditions is met simultaneously, the failure is determined to be brittle interface peeling failure: (1) The rate of change of impedance modulus in the characteristic parameters of impedance spectrum exceeds the first preset rate of change threshold in the first preset time period before the load reaches the peak value, and the phase angle offset exceeds the first preset offset threshold in the second preset time period. (2) The growth rate of the cumulative ring count in the acoustic emission signal exceeds the first preset growth rate threshold during the third preset time period, while the growth rate before the third preset time period is lower than the second preset growth rate threshold. (3) In the maximum principal strain cloud map obtained after digital image correlation calculation, there is a continuous high strain band in the bonding interface region. The width of the continuous high strain band is less than the first preset width threshold, and the coverage of the continuous high strain band in the entire length direction of the bonding interface exceeds the first preset coverage threshold.

[0038] If the following second set of conditions are met simultaneously, the failure is determined to be ductile matrix fracture: (1) The rate of change of impedance modulus in the characteristic parameters of impedance spectrum is lower than the second preset rate of change threshold throughout the entire process of load application, and the rate of change of phase angle offset is lower than the second preset offset threshold throughout the entire process of load application. (2) The second derivative of the cumulative ringing count curve in the acoustic emission signal is positive, and the rate of change of its first derivative continues to decrease throughout the entire process of load application; (3) In the maximum principal strain cloud map obtained after digital image correlation calculation, there are at least two high strain concentration areas that are separated from each other. The area of ​​each high strain concentration area is less than the second preset area threshold, and the minimum distance between any two high strain concentration areas is greater than the preset distance threshold. There is no continuous high strain zone that covers the entire length of the bonding interface and exceeds the second preset coverage threshold.

[0039] In this embodiment, under the conditions of 6% epoxy resin content, 50% recycled aggregate replacement rate, and grooved interface treatment, the NC-PARAC bonded specimen exhibited an impedance modulus change rate consistently lower than the second preset change rate threshold (measured maximum change rate <15% / second) throughout the entire loading process, and a phase angle offset change rate lower than the second preset offset threshold (<5° / second). The second derivative of the cumulative ringing count curve was positive, and the first derivative continuously decreased. Three separate high-strain concentration zones (each with an area of ​​12mm) were observed in the maximum principal strain contour map. 2 8mm 2 15mm 2 All are less than the preset area threshold of 30mm 2 Furthermore, the distance between any two zones is greater than 5 mm, and there is no continuous high strain band that extends more than 50% of the total length of the bonding interface. Therefore, it is determined to be a ductile matrix fracture failure.

[0040] For NC-PARAC bonded specimens (n=5) prepared in the same batch, online detection was performed using the above method, and the results were compared with the observations of the interface microstructure (SEM, MIP) after damage. The results show that the damage stage determined by the method of this invention is highly consistent with the evolution law of the micropore structure (correlation coefficient R). 2 =0.94); the determined failure mode matches the actual fracture morphology (rough ductile fracture interface, with a matrix slurry adhesion area >70%; smooth brittle fracture interface, with an adhesion area <20%). This verifies the feasibility and accuracy of the invention.

[0041] Example 2 The difference between this embodiment and Embodiment 1 is that: no interface agent is applied to the NC bonding interface, and a deep groove treatment is adopted (groove depth 12mm, spacing 15mm).

[0042] The test results show that in this embodiment, the rate of change of impedance modulus abruptly jumps from 23% to 68% in the last 5 seconds before the load reaches its peak, exceeding the first preset rate of change threshold (preset to 50% / 5 seconds in this embodiment). Simultaneously, the phase angle shift changes by 12° within 1 second, exceeding the first preset shift threshold (preset to 10° / second). The cumulative acoustic emission ring count increases by 85% in the last 5 seconds, exceeding the first preset growth rate threshold (preset to 50% / 5 seconds), while the growth rate before this period is 8%, lower than the second preset growth rate threshold (preset to 20% / 5 seconds). In the maximum principal strain cloud map obtained from digital image correlation calculation, a continuous high-strain band with a width of 1.5 mm and a full length coverage of 95% is formed in the bonding interface region. This width is less than the first preset width threshold (preset to 2 mm), and the coverage exceeds the first preset coverage threshold (preset to 80%). All three condition groups meet the first condition group's criteria, therefore, the failure is determined to be brittle interface peeling. This method can still effectively identify damage stages and failure modes.

[0043] Example 3 The difference between this embodiment and Embodiment 1 is that the epoxy resin content in the PARAC mix proportion is 0% (i.e., no epoxy resin is added), and the recycled aggregate replacement rate is 100%.

[0044] The test results show that in this embodiment, the rate of change of impedance modulus exhibited multiple abrupt changes throughout the loading process, with the highest rate of change reaching 78% / second, exceeding the second preset rate of change threshold (preset to 20% / second in this embodiment). The rate of change of phase angle offset also showed multiple steps, with the maximum rate of change being 18° / second, exceeding the second preset offset threshold (preset to 8° / second). The first derivative of the acoustic emission cumulative ringing count curve continuously increased, while the second derivative was negative, failing to meet the requirements for the cumulative ringing count curve in the second condition group. The maximum principal strain cloud map showed a continuous high-strain band extending 90% of the entire length of the bonding interface, exceeding the second preset coverage threshold (preset to 50%). The above indicators do not meet the second condition group but meet the characteristics of the first condition group, therefore, it is determined to be brittle interface peeling failure. The rate of change of comprehensive indicators at each damage stage is significantly accelerated (the total time from elastic deformation to complete failure is shortened by approximately 60% compared to Example 1). The method of this invention can still effectively detect the damage evolution process.

[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An online detection method for NC-PARAC bond interface damage based on impedance spectroscopy, characterized in that, Includes the following steps: S1. Apply an AC excitation signal within a preset frequency range to the bonding interface region of the NC-PARAC bonded specimen, and collect the initial impedance spectrum of the bonding interface region in a non-destructive state, including the initial impedance magnitude and the initial phase angle. S2. Apply a monotonically increasing load to the NC-PARAC bonded specimen. During the loading process, collect the acoustic emission signals released by the NC-PARAC bonded specimen during deformation and failure, as well as the digital image sequence of the NC-PARAC bonded specimen surface. At the same time, continuously collect the real-time impedance spectrum of the bonding interface region at preset time intervals, including the real-time impedance modulus and real-time phase angle. S3. Compare and calculate the acquired real-time impedance spectrum with the initial impedance spectrum, and extract the characteristic parameters of the impedance spectrum, including the rate of change of impedance magnitude, phase angle offset, and the change of the real part of impedance at characteristic frequency points. S4. Perform event alignment processing and data correlation analysis on the collected acoustic emission signals, digital image sequences and extracted impedance spectrum feature parameters to construct comprehensive damage characterization indicators, including interface pore connectivity, microcrack density and interface transition zone degradation index. S5. Compare the constructed comprehensive damage characterization index with the preset damage threshold library to determine the current damage state of the bonding interface region of the NC-PARAC bonded specimen, including the elastic deformation stage, microcrack initiation stage, crack stable propagation stage, crack unstable penetration stage, and complete failure stage. S6. Based on the changing trends of comprehensive damage characterization indicators, identify the failure modes of the NC-PARAC bonding interface, including brittle interface peeling failure and ductile matrix fracture failure.

2. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In step S3, before extracting the impedance spectrum characteristic parameters, a moving average filter with a preset window length is used to smooth the real-time impedance spectrum. An impedance spectrum fitting method based on an equivalent circuit model is used to extract the interface charge transfer resistance and the interface double layer capacitance. The equivalent circuit model is composed of solution resistance, interface charge transfer resistance, interface double layer capacitance, and constant phase angle elements connected in series or in parallel.

3. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In step S4, the interface pore connectivity is calculated as follows: based on the rate of change of impedance modulus and the phase angle offset in the impedance spectrum characteristic parameters, and combined with a preset pore structure-impedance response mapping model, the interface pore connectivity is calculated. The pore structure-impedance response mapping model is established based on Maxwell-Garnett effective medium theory or Bruggeman effective medium theory.

4. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In step S4, the microcrack density is calculated as follows: the acoustic emission signal is processed by parameter extraction to obtain the ring count, cumulative ring count, energy count and amplitude distribution; digital image correlation calculation is performed on the digital image sequence to obtain the maximum principal strain distribution in the whole field; and spatiotemporal correlation analysis is performed on the ring count, cumulative ring count, energy count, amplitude distribution and the maximum principal strain distribution in the whole field to calculate the microcrack density.

5. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 4, characterized in that: The specific steps for performing digital image correlation calculations on digital image sequences are as follows: a speckle field with random gray-scale distribution is set on the surface of the NC-PARAC bonded specimen. Using the reference image before loading as a benchmark, the zero-mean normalized cross-correlation algorithm is used to perform subset matching processing on the deformed image after loading to obtain the displacement field of the whole field. The displacement field is then spatially differentiated to obtain the strain field of the whole field. The maximum principal strain distribution is extracted from the strain field of the whole field.

6. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In S4, the interface transition zone degradation index is calculated as follows: based on the change in the real part of the impedance at the characteristic frequency point in the impedance spectrum characteristic parameters, combined with the cumulative ringing count in the acoustic emission signal and the strain localization bandwidth in the digital image sequence, the interface transition zone degradation index is obtained through weighted fusion calculation. The weight coefficients of each index in the weighted fusion calculation are determined based on the principal component analysis method or the entropy weight method.

7. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In step S5, the preset damage threshold library is established as follows: destructive tests are conducted on NC-PARAC bonded specimens with different recycled aggregate replacement rates and different epoxy resin contents in different groups. During the destructive test, impedance spectra, acoustic emission signals, and digital image sequences are collected simultaneously. The collected data are correlated with the observation results of the interface microstructure after damage. Threshold intervals for impedance spectrum characteristic parameters, acoustic emission signal characteristic parameters, and digital image related characteristic parameters corresponding to each damage stage are established to form a preset damage threshold library.

8. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In S6, the specific criteria for identifying the brittle interface peeling failure mode are as follows: the rate of change of impedance modulus in the impedance spectrum characteristic parameters exceeds a first preset rate of change threshold in a first preset time period before the load reaches its peak value; the phase angle offset exceeds a first preset offset threshold in a second preset time period; the growth rate of the cumulative ringing count in the acoustic emission signal exceeds a first preset growth rate threshold in a third preset time period, while the growth rate before the third preset time period is lower than a second preset growth rate threshold; and in the maximum principal strain cloud map obtained after digital image correlation calculation of the digital image sequence, there is a continuous high strain band in the bonding interface region, the width of the continuous high strain band is less than a first preset width threshold, and the coverage of the continuous high strain band in the entire length direction of the bonding interface exceeds a first preset coverage threshold.

9. The online detection method for NC-PARAC bond interface damage based on impedance spectroscopy according to claim 1, characterized in that: In S6, the specific criteria for identifying the fracture failure mode of the ductile matrix are as follows: the rate of change of the impedance modulus in the impedance spectrum characteristic parameters is lower than the second preset rate of change threshold throughout the entire process of load application; at the same time, the rate of change of the phase angle offset is lower than the second preset offset threshold throughout the entire process of load application; the second derivative of the cumulative ringing count curve in the acoustic emission signal is positive; the rate of change of its first derivative continuously decreases throughout the entire process of load application; and in the maximum principal strain cloud map obtained after digital image correlation calculation of the digital image sequence, there are at least two high strain concentration areas that are separated from each other, the area of ​​each high strain concentration area is less than the second preset area threshold, the minimum distance between any two high strain concentration areas is greater than the preset distance threshold, and there is no continuous high strain band that covers the entire length of the bonding interface and exceeds the second preset coverage threshold.